The regulation of crowdfunding: regarding emergency Decree 013-2020 which establishes the legal regime for financial crowdfunding - Jiménez Alemán, José Alonzo (2021)
The financing market is one of the cornerstones for the promotion of entrepreneurship, innovation and job creation. In this regard, participatory financing (also known as crowdfunding) is positioned as an important credit tool that, among other characteristics, through technological innovation, creates a flexible ecosystem of direct intermediation that allows investors and promoters to connect on a massive scale. At the same time, it ensures an effective competition of financing sources in the credit market.In this article, the author presents a general framework on crowdfunding and critically analyzes its regulation in the Peruvian legal system. Along the same lines, taking into consideration comparative experience, he proposes some regulatory recommendations in order to promote the growth of crowdfunding and ensure its proper functioning in the market.